Dynamic capability of servant leadership as a triggering factor for organizational commitment and employee performance - Muhamad Teguh Setiadi; Wahyudi Wahyudi; Didit Haryadi; Imam Sofi’i (Trigin Publisher, 2023)
Among effective management systems, the importance of human resources is increasing. Employee performance is an essential factor that influences success. In an organization, it is one of the most critical functions of an agency. This research aims to determine the variables that affect employee performance and develop a theoretical basis and research model. This research used an associative descriptive quantitative method with a population of 244 respondents, employees of the Public Works and Spatial Planning Department, and a sample of 150 respondents who were employees of the Public Works and Spatial Planning Department with probability sampling using the proportional stratified random sampling method. One hundred fifty questionnaire data have been obtained and processed. The results of this research show that the first hypothesis is that employee performance is significantly influenced by servant leadership, the second hypothesis is that organizational commitment is influenced considerably by servant leadership, the third hypothesis is that employee performance is influenced substantially by organizational commitment, the fourth hypothesis is that organizational commitment can mediate the influence of servant leadership on employee performance. It is hoped that this research can provide a theoretical contribution to the literature in this context, of course, in the context of human resource management.